Overview Of Supervision Of The Performance Of Health Workers At Badrul Aini Hospital - Rara Fristi Arsania; Indah Doanita Hasibuan; Yulia Adinda Nasution; Syafirda Alifah Lubis; Sukma Khairani Sihombing (International Journal Of Health Science, 2024)
Hospitals as Health Institutions have a strategic role in improving the health status of the Indonesian people. Human resources are a key factor in health services, requiring competent workforce and supported by fellow colleagues. Monitoring is an important step in ensuring the realization of management plans. Employee performance, especially health workers, is a key factor for hospitals, influencing the institution's ability to achieve its goals. This study aims to evaluate the supervision of the performance of health workers at Badrul Aini Hospital, with a focus on improving medical services. In the context of population growth, medical services by public hospitals are crucial. This research used a quantitative approach with descriptive methods, involving 30 respondents from all hospital health workers. The research results show high patient satisfaction regarding the performance of health workers. Discussion includes the role of human resources, the positive impact of supervision on performance, and the need for direct management to improve the performance of public hospital employees.